Antigua y moderna artesanía ayacuchana - Cruz Morote, Nelva de la ([Perú] : Lluvia Editores, 2018)
Since colonial times, the presence of popular artists, artisans, sculptors and imagery has been predominant both in the city of Huamanga and in the surrounding towns and villages. For example, a record of 1827 mentions the existence of 38 silversmiths, 10 buttons and embroiderers, 103 workers, galoneros and rows (chullapa), 65 hatters, 56 tanners, 4 potters and potters, 14 tablecloths, 14 painters and sculptors and 8 cereros . More than a hundred years later, a recount of occupations carried out by the Municipality of Huamanga includes the presence of 33 tanners, 29 colcheros, 11 sculptors, 55 frazaderos, 4 jewelers, 5 adorners, 16 silversmiths, 4 hatters and 2 saddle makers. For the years after the middle of the twentieth century, the present text of Nelva de la Cruz Morote gives an account of the popular artists existing in the city and in jurisdictions specialized in folk art, such as the town of Quinua.
Prólogo -- Antigua y moderna artesanía Huamanga -- La artesania en Ayacucho -- La artesania -- Situación actual de la artesania ayacuchana -- Relación de artesanos Huamanga y Quinua -- Relación de artesanos encuestados por zonas -- La textileria -- Retablos -- Anexo No. 2 -- Lista de talleres de Unidades de Producción Artesanal -- Asociación de artesanos "Juan Velasco Alvarado" -- Ultima asociación de artesanos "Libertadores Wari" -- Relación de Artesanos libertadores Wari - Ayacucho.
In Spanish.
Keywords: Folk art -- Peru -- Ayacucho; Handicraft -- Peru -- Ayacucho; Artisans -- Peru -- Ayacucho; Ayacucho (Peru) -- Social life and customs